Converting Access Microbiology to an open research platform: community survey results. Issue 9 (8th September 2021) - Howat, Alexandra M.; Clark, Justin
Abstract : Following the Microbiology Society's successful bid for a Learned Society Curation Award from the Wellcome Trust and Howard Hughes Medical Institute, the Society is converting our sound science, open access journal, Access Microbiology, to an open research platform. As part of this, we conducted a survey of our community to gauge current attitudes towards the platform and here we present some of these results. The majority of respondents (57 %) said they would always or sometimes want to remain anonymous on their peer review report, whilst 75 % of respondents said that as an author they would be happy to make the data underlying their research open. There was a clear desire for a range of research types that are often seen with sound science publications and rigorous research. An encouraging 94 % of respondents stated that the platform is somewhere they would consider publishing, demonstrating the enthusiasm in these respondents for a new publishing platform for their community. Given this data and that from our previous focus group research, the platform will launch as outlined in the original project proposal and adopt a transparent peer review model with an open data policy.